Fine-tuning the theoretically predicted structure of MIL-47(V) with the aid of powder X-ray diffraction. Issue 45 (17th September 2015) - Bogaerts, Thomas; Vanduyfhuys, Louis; Vanpoucke, Danny E. P.; Wieme, Jelle; Waroquier, Michel; Van Der Voort, Pascal; Van Speybroeck, Veronique
Abstract : The structural characterization of complex crystalline materials can be simplified by closely comparing theoretical and experimental diffraction patterns. Abstract : The structural characterization of complex crystalline materials such as metal organic frameworks can prove a very difficult challenge both for experimentalists as for theoreticians. From theory, the flat potential energy surface of these highly flexible structures often leads to different geometries that are energetically very close to each other. In this work a distinction between various computationally determined structures is made by comparing experimental and theoretically derived X-ray diffractograms which are produced from the materials geometry. The presented approach allows to choose the most appropriate geometry of a MIL-47(V) MOF and even distinguish between different electronic configurations that induce small structural changes. Moreover the techniques presented here are used to verify the applicability of a newly developed force field for this material. The discussed methodology is of significant importance for modelling studies where accurate geometries are crucial, such as mechanical properties and adsorption of guest molecules.